1993
DOI: 10.1007/bf01111269
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in broiler chicks on feed amended withFusarium proliferatum culture material or with purified fumonisin B1 and moniliformin

Abstract: Two hundred twenty-eight male chicks (Columbia x New Hampshire) were given feed amended with autoclaved culture material (CM) of Fusarium proliferatum Containing fumonisin B1 (FB1), fumonisin B2 (FB2) and moniliformin in 3 separate feeding trials. Purified FB1 and moniliformin were given separately and in combination in a fourth feeding trial. Birds were given amended rations at day 1 (Trial 1 and 4), day 7 (Trial 2), and day 21 (Trial 3) and their respective ration was given for 28 days (Trial 1), 21 days (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 27 publications
2
50
3
Order By: Relevance
“…leucocyte and red blood cell counts), food or water consumption, or organ or body weights compared to the negative controls. This result differs from previous reports of reduced feed intake and body weights of test animals such as turkeys, broiler chicks and barrows (Allen et al, 1981;Harvey et al, 2001;Javed et al, 1993). The contrasting outcome is most likely due to differences between species.…”
Section: Discussioncontrasting
confidence: 86%
“…leucocyte and red blood cell counts), food or water consumption, or organ or body weights compared to the negative controls. This result differs from previous reports of reduced feed intake and body weights of test animals such as turkeys, broiler chicks and barrows (Allen et al, 1981;Harvey et al, 2001;Javed et al, 1993). The contrasting outcome is most likely due to differences between species.…”
Section: Discussioncontrasting
confidence: 86%
“…Several studies have suggested that the mycotoxins could have synergistic effect in vivo (Bacon, Porter, Norred, & Leslie, 1996;Javed et al, 1993), therefore the knowledge of the occurrence of all mycotoxins should be considered a challenge in exposure assessment studies. In our work, the co-occurrence of different mycotoxins in the same sample, was studied considering positive those samples above LOD (Table 4).…”
Section: Co-occurrence Of Trichothecenes In the Samplesmentioning
confidence: 99%
“…The standards of the two compounds prepared from the crude extract showed identical retention time in HPLC. For separation of these compounds, the three-phase solvent system composed of n-hexane-acetonitrile-dichloromethane-water at a volume ratio of 5:5:1:2 was considered for preparation of the HSCCC combination columns, because it showed a high capacity to dissolve the natural products [8]. Based on this solvent system, four other stable three-phase solvent systems with further improved phase volume ratio and capacity to dissolve the sample were developed by increasing the volume ratio of water to 5 and adding ethyl acetate.…”
Section: Selection Of Solvent Systemmentioning
confidence: 99%